Efektivitas Konsumsi Moringa Oliefera Untuk Menurunkan Kadar Gula Darah Penderita Diabetes Mellitus: Meta-Analisis - Fatimah Rahmawati; Anisa Andriani; Yessy Widhi Astuti; Franciscus Xaverius; Fatimah Wahyu; Fatimah Hasna Karima; Niken Putri Eka Saraspuri; Afifah Noer (Universitas Dharma Wacana, 2026)
Diabetes Mellitus (DM) is a metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. The most common type of diabetes, accounting for approximately 90% of all cases, is type 2 DM. Diabetes management can be carried out with non-pharmacological therapies. One such therapy is the use of herbal plants as an additional therapy in controlling blood glucose levels using Moringa oleifera leaves, which have antidiabetic potential. The content of Moringa oleifera leaves can lower blood glucose levels. The purpose of this study was to determine the effectiveness of Moringa oleifera consumption in reducing DM. This research method used meta-analysis and systematic review with Randomized Controlled Trial (RCT) studies. A total of 7 articles were used in the quantitative analysis (meta-analysis) originating from two African continents, one European continent, and four from the Asian continent. The results showed that consuming Moringa oleifera significantly reduced blood glucose levels with a SMD value of -0.83 (95% CI: -1.51 to -0.14; p = 0.02). In conclusion, Moringa oleifera has the potential to be used as a complementary therapy in the management of diabetes mellitus, but cannot yet replace the main therapy that has been clinically recommended. It is recommended that the use of Moringa oleifera can be considered and utilized by diabetes mellitus patients as part of a healthy lifestyle.